Caracterização Econômica e Mercadológica da Região Produtora de Rochas Ornamentais de Santo Antônio de Pádua ( RJ) - João Baptista Filho; Maíra Damião Tanaka (Anuário do Instituto de Geociências, 2002)
This paper is an attempt to delineate the ways of nowadays industrialization of ornamental Rocks in Santo Antônio de Pádua (RJ) It is very important to emphasize the almost total dependence of the local economy with this kind of activity.